Sinbad : legend of the seven seas [videorecording (DVD)] - Logan, John, 1961-; Fiennes, Joseph, 1970-; Gregson-Williams, Harry (Universal Pictures Home Entertainment, 2018)
Sinbad, a daring and notorious rogue, has spent his life sailing the seven seas asking for trouble. Now he has been framed for stealing a priceless and powerful treasure--the Book of Peace. Sinbad has one chance to find and return the precious book, and battle the Goddess of Chaos or his best friend Proteus will die.